Effect of final rolling temperature on the microstructure and properties of high-manganese austenitic low-temperature steel - Peng Zhang; Ling Yan; Xuemin Wang; Xiangyu Qi; Xiangyu Xu; Pengcheng Liu; Xueliang Shang; Jinyi Liu; Chengjia Shang (Journal of Materials Research and Technology, 2024)
The effect of final rolling temperature ranging from 962 to 696 °C on as-rolled high-Mn austenitic low-temperature steel was investigated using scanning electron microscopy, electron backscatter diffraction, transmission electron microscopy, and X-ray diffraction. The microstructure of the experimental steel remained austenite without suffering ferrite phase transformation, even when produced with a final rolling temperature as low as 696 °C. A decrease in the final rolling temperature of the steel was accompanied by a decrease in grain size from 20.2 to 6.0 μm, accompanied by an increase in dislocation density from 3.01 × 1014 to 10.9 × 1014 m−2. In addition, M23C6 carbides precipitated at the grain boundaries when the final rolling temperature was below 782 °C. Grain refinement and increased dislocation density significantly enhanced the strength of the material. However, an increase in the intragranular dislocation density compromised grain deformation ability. Moreover, the precipitation of M23C6 reduced the plasticity and toughness of the material. Considering the balance between yield strength and low-temperature toughness, the optimal final rolling temperature was 898 °C; this produced a material with a yield strength of approximately 507 MPa and a low-temperature impact energy absorption of approximately 143 J.